Nostalgia and Poetry: Reflections on Research, Creative Expression, and Fieldwork Across Borders - Motapanyane, Maki (Atlantis, 2013)
This paper takes an interdisciplinary theoretical approach to methodological consider-ations of insider/outsider status in the context of transnational research projects. The focus is on expatriate nostalgia in relation to feminist research. Poetry, in the form of fieldwork journal, is presented as a productive outlet for nostalgia—a method of feminist self-reflexivity that can strengthen the researcher’s critical intuition, clarify standpoint and interpretive approach, and mediate the condition of multiple belonging. In the context of fieldwork conducted in South Africa in affiliation with a Canadian university, expatriate nostalgia is highlighted as a neglected area of feminist methodological inquiry. The paper further considers the productive potential of creative expression to the process of negotiating identity, dissecting power relations, and tran-scending dichotomous understandings of insider/outsider status in the context of academic research.